Luminescent Probe Based on Terbium-Carbon Quantum Dots for the Quantification of Imidacloprid in Caneberries - Eulogio J. Llorent-Martínez; Julia Jiménez-López; Antonio Ruiz-Medina (Journal of Analytical Methods in Chemistry)
We propose a modification of terbium-sensitized luminescence (TSL) by means of the introduction of nanoparticles to improve the sensitivity and selectivity of the analytical methods. TSL detection is usually based on the complexation between fluorescent organic compounds (the analytes) and terbium. The organic compound is then excited, and, after an energy transfer towards terbium, the latter emits the luminescence signal. Here, the modification consists of the introduction of nanoparticles (carbon quantum dots, CQDs) into the system. The carboxylic groups of CQDs react with terbium, providing an interesting time-resolved luminescence probe. We applied this system for the determination of the neonicotinoid imidacloprid (IMID). When IMID was introduced in the terbium-CQDs system, the luminescent signal (λexc/λem of 256/545 nm) was quenched, proportionally to IMID concentration in the range of 100–2500 ng·mL−1, obtaining a limit of detection of 30 ng·mL−1. A method detection limit of 0.9 mg·kg−1 was reached in caneberries, thus complying with the maximum residue level of 5 mg·kg−1 established by Codex Alimentarius. We performed recovery experiments in caneberries (blackberries, blueberries, raspberries, and mulberries), obtaining recovery yields close to 100% in all cases. These results show that the use of terbium ions-nanoparticles luminescence probes can be useful for screening purposes in quality control laboratories.